Effectiveness Management Communication Countermeasures Cross–Sectoral Disasters: A Study Empirical Digital Era - Yusnizar, Yusnizar; Zulher, Zulher; Marantika, Abshor (Dinasti International Journal of Economics, Finance & Accounting, 2026)
Effective interaction serves as a critical component in disaster mitigation strategies, encompassing stages from prevention and readiness to crisis handling and post-event restoration. This scenario necessitates a robust, efficient, and versatile framework for disaster response that aligns with evolving technological advancements. The analytical process employed the Miles and Huberman framework, involving steps such as condensing information, organizing displays, and deriving insights through validation, supported by multi-source and multi-method cross-verification. Key observations include: (1) The Kampar Disaster Management Agency (BPBD) has initiated the integration of electronic tools, yet cross-agency coordination remains fragmented, constraining practical outcomes—primary barriers encompass duplicated responsibilities, insufficient tech proficiency among personnel, and inadequate facilities; (2) A blended strategy incorporating both operational and supportive measures is essential to enhance precision and responsiveness in interventions; (3) The success of inter-agency dialogue coordination during the tech-driven period hinges on collaborative efforts among stakeholders, precise delineation of organizational duties, and maximized deployment of digital resources; (4) Despite the incorporation of modern tech solutions, the Kampar BPBD's inter-sectoral coordination for disaster handling continues to encounter various hurdles.